A Systematic Survey of Control Groups in Behavioral and Social Science Trials. (July 2018) - Wang, Mei; Sun, Guangwen; Chang, Yaping; Jin, Yanling; Leenus, Alvin; Maaz, Muhammad; Li, Guowei; Bhatt, Meha; Abbade, Luciana P. F.; Nwosu, Ikunna; Zielinski, Laura; Sanger, Nitika; et al.
Behavioral and social sciences randomized controlled trials (BSSTs) have a significant role in life sciences. Choosing an appropriate control or comparator group for BSSTs is critical, to provide true intervention effects. The objective of this study was to determine the types of control groups used in BSSTs, and the rationale provided to justify these choices. We conducted a systematic survey of BSST protocols published between January 2012 and October 2016 in the Cochrane Library and Medline databases. We randomly selected 200 protocols. The study selection and data extraction were performed independently in duplicate. The most frequent control groups were active concurrent (97/200, 48.5%), and no treatment concurrent controls (88/200, 44.0%). The majority of studies (71.5%) did not provide justification for comparators choice. We concluded that BSSTs trials compare interventions to active and no treatment controls however the majority of trials lacked rationale for the selection of the study comparator.